Expendable or valuable? Photojournalism in five Swedish newspapers affected by organizational changes - Nilsson, Maria (Journalistica, 2021)
This study explores the impact of organizational changes on newspaper photo departments, an area of newsrooms that have arguably been particularly affected by structural changes in the field of journalism Through qualitative interviews with editors responsible for photojournalism at five Swedish newspapers that have experienced recent changes to photo staffing and routines for the sourcing of images, the study explores the following questions: Which routines do the newspapers have for sourcing images, in terms of in-house staff and external sources? How do notions of visual quality and external factors, such as audiences and competition, contribute to shaping the newspapers’ visual strategies? Findings indicate that newspapers rely on staff photojournalists for unique and in-depth coverage, but less for routine and breaking news. A certain expansion of photojournalism was found in some newsrooms where it is seen as a competitive edge; which, in part, challenges a “discourse of doom.” Uncertainty about the support for visual strategies in newsrooms lacking visual leadership was also found.